ANALYZING THE STUDENTS’ ENGLISH ACHIEVEMNET THROUGH COOPERATIVE GROUP DISCUSSION - Apriana, Apriana (Esteem Journal of English Education Study Programme, 2022)
The goal of this study was to make students able to communicate fluently using English in everyday life, using cooperative group discussion strategies to make students more active in interacting with others. To collect the data for this research, the writer used interview and questionnaire with the eighth grade students at junior high school 2 of Palembang. Each student will be given a paper like a questionnaire. The author discussed the results of the research that has been done, namely using the cooperative group discussion technique in learning speaking skills of students in the eighth grade. From the results of the questionnaire data processing, it can be concluded that cooperative group discussion techniques can improve students ''speaking skills". Most of the students (50%) of the 16 respondents answered fully agree, while the rest chose 8 (50%) of the 16 respondents answered agree. Then the dominant result is balanced. The overall results of the study showed that cooperative group discussions can effectively improve students' speaking skills, they actively conduct cooperative discussions with their friends. Allow them to have an opinion and help each other, without mocking or laughing at each other.